MULTI-TIME-SCALE VARIABILITY OF STARS - Andronov, I. L. (Одеські астрономічні публікації, 2017)
Physical mechanisms and corresponding mathematical models for different types of stellar variability are reviewed with applications to concrete stars. Special attention is attributed to the following topics: cataclysmic variables (synchronous and synchronizing magnetic systems, non-magnetic novalike stars, dwarf novae; magnetic activity of the red companion, third body around), pulsating variables (additional classification criteria of variability, multiparameter correlation analysis of the characteristics of the mean light curves of groups of long-period stars and of the multi- parameter correlation analysis of the individual characteristics of their pulsations), mathematical models (multi-periodic, multi-harmonic, multi-shift variations with possible trends, mono- and multi- cyclic variations of low coherence and the frequency changing/switching signals, "red noise" variability. Some original papers and links may be found at http://ila.webjump.com